2008
DOI: 10.4088/pcc.v10n0603
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Efficacy of Adjunctive Aripiprazole in Major Depressive Disorder

Abstract: www.clinicaltrials.gov Identifiers: NCT00095823 and NCT00095758.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…These SSRI subgroup data were provided for two of the trials 47,50 for the outcome of mean change in MADRS score 14 from baseline at study end point from a pooled analysis. 62 Other corresponding authors either did not reply or were unable to provide data on this subgroup.…”
Section: Assessment Of Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…These SSRI subgroup data were provided for two of the trials 47,50 for the outcome of mean change in MADRS score 14 from baseline at study end point from a pooled analysis. 62 Other corresponding authors either did not reply or were unable to provide data on this subgroup.…”
Section: Assessment Of Effectivenessmentioning
confidence: 99%
“…These trials comprised data from the six trials 30,49,52,53,59 in the primary analysis on the comparison of SSRI (or venlafaxine) + quetiapine with SSRI (or venlafaxine) + lithium, as well as data from the three SSRI (or venlafaxine) + aripiprazole trials compared with SSRI (or venlafaxine)-alone trials. 47,48,50 The data from two of the SSRI + aripiprazole compared with SSRI-alone trials, 47,50 were available as a pooled analysis 62 that was broken down by individual SSRI, and so these data were included as this enabled the exclusion of the data from patients with baseline venlafaxine treatment, thus reducing the amount of potential clinical heterogeneity. The random rather than fixed-effects model was deemed to be the best fitting (DIC 45 vs. 47, respectively) and resulted in a MD of 1.27 (95% CrI -1.88 to 4.68) for SSRI + lithium compared with SSRI + AAP.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Category C recommendations include psychostimulants and anticonvulsants. It must be noted that the BAP guidelines were formulated before the current body of evidence for aripiprazole and quetiapine was available [22][23][24]. The ICSI healthcare guidelines were developed for the treatment of major depression in primary care in the USA [11].…”
Section: Augmentation Strategies In Other Guidelinesmentioning
confidence: 99%
“…Our study is the first one, which has investigated aripiprazole's efficacy with the CMS model. Additionally, the sucrose consumption test is considered as the best match of anhedonia in animals which is a good predictor of human depression 37,38 . Clinical trials of aripiprazole have revealed that it is effective in resistant depression, bipolar depression and major depression.…”
Section: Discussionmentioning
confidence: 99%